Improved MALDI‐MS method for the highly sensitive and reproducible detection of biomarker peaks for the proteotyping of Salmonella serotypes. (27th November 2019) - Fukuyama, Yuko; Ojima‐Kato, Teruyo; Nagai, Satomi; Shima, Keisuke; Funatsu, Shinji; Yamada, Yoshihiro; Tamura, Hiroto; Nomura, Shizuo; Ogata, Koretsugu; Sekiya, Sadanori; Iwamoto, Shinichi; Tanaka, Koichi
Abstract: The rapid identification and classification of pathogenic microorganisms, including Salmonella enterica, is important for the surveillance and prevention of foodborne diseases. Matrix‐assisted laser desorption\ionization time‐of‐flight mass spectrometry (MALDI‐TOFMS) has been shown to be an effective tool for the rapid identification of microorganisms. In a previous report, a mass database consisting of 12 biomarker proteins, S8, L15, L17, L21, L25, S7, superoxide dismutase (SodA), peptidylprolyl cis‐trans isomerase C, Gns, YibT, YaiA, and YciF, was introduced for the serotyping of S. enterica via MALDI‐MS ( Applied Microbiology and Biotechnology, 2017, 101, 8557‐8569). However, the reproducibility of peak detection of biomarkers such as SodA at m\z 23 000 was poor. We report here an optimized MALDI‐MS method for detecting these biomarkers with high sensitivity and reproducibility. The issue was solved by controlling the bacterial concentration at 1 × 10 to 1 × 10 2 MFU (3 × 10 6 to 3 × 10 7 CFU\μL, as calculated from the MFU), using the colony suspension supernatant obtained by centrifugation, and using matrix additives such as methylenediphosphonic acid and N ‐decyl‐ β ‐D‐maltopyranoside. We propose that the method including the above steps is one of the best for detecting biomarkers with high sensitivity and reproducibility.